Motivational styles and instructional designs of second language learning : a brief insight into students' language learning preferences / Francis Xavier A.S.Rajoo - A.S. Rajoo, Francis Xavier (Universiti Teknologi MARA Kedah, Sungai Petani, 2002)
This article gives a brief insight into certain components of motivational styles, which are viewed as important aspects that can influence language learning processes. The focus is on two best known constructs of motivation (instrumental and integrative motivation), as well as the interrelationship between the levels of motivational styles and three types of instructional designs (traditional, communicative and integrated orientation) usually used by English language teachers. A small-scale research was conducted and its findings indicated that there is a significant interrelationship between the levels of motivational styles, and certain instructional designs commonly utilised in English language teaching.